Pengaruh Penggunaan E-Procurement Terhadap Efektifitas Dan Efisiensi Pengadaan Barang/Jasa Pada Kantor Layanan Pengadaan Barang/Jasa Pemerintah Kabupaten Bogor - Sari, Amalia; ., Triandi (Institut Bisnis dan Informatika Kesatuan, 2016)
Procurement of goods/services is an activity to obtain goods/services by the Ministry/Institution/Regional Working Units/Institutions that started from the process of planning requirements until completion of all activities to obtain goods/services. Procurement of goods/services must be carried out in an efficient, effective, transparent, open, competitive, fair/non-discriminatory and accountable in accordance with the Decree of the President of the Republic of Indonesia Number 70 Year 2012 concerning the second amendment of Presidential Decree Number 54 Year 2010 on the procurement of goods/services of the government. In order to realize this, institutions apply e-procurement. E-procurement is the procurement of goods/services that are implemented using information technology and electronic transactions in accordance with statutory provisions. The purpose of this study was to determine the effect of e-procurement on the effectiveness and efficiency of the procurement of goods/services. Research was conducted at Kantor Layanan Pengadaan Barang/Jasa Pemerintah Kabupaten Bogor located in Nyaman’s Street No. 01 Tengah Cibinong Bogor. It is an organizational unit of the Ministry/Agency/Local Government/Institutions that function at implementing permanent procurement of goods/services, and can work independently or attached to other existing unit. The results showed that there is a positive and significant effect in the use of e-procurement on the effectiveness and efficiency of the procurement of goods/services at Kantor Layanan Pengadaan Barang/Jasa Pemerintah Kabupaten Bogor